Risk factors in childhood arterial ischaemic stroke: Findings from a population-based study in Germany. (May 2018) - Gerstl, Lucia; Weinberger, Raphael; von Kries, Ruediger; Heinen, Florian; Schroeder, A. Sebastian; Bonfert, Michaela V.; Borggraefe, Ingo; Tacke, Moritz; Vill, Katharina; Landgraf, Mirjam N.; Kurnik, Karin; Olivieri, Martin
Abstract: Objective: Acute treatment of childhood arterial ischaemic stroke and prevention strategies for recurrent stroke episodes depend strongly on each child's individual risk profile. The aim of this study is to characterize risk factors for childhood stroke, their occurrence in isolation or combination, and to identify possible common risk factor patterns. Methods: This population-based study was conducted via ESPED, a surveillance unit for rare paediatric diseases in Germany. Children aged >28days and <18 years with an acute arterial ischaemic stroke occurring between January 2015 and December 2016 were included. Results: Among 99 reported children with arterial ischaemic stroke, 56 children were male. Male predominance was significant in adolescents from 12 years old onward. Arterial ischaemic stroke was more common in very young children <2 years of age and in adolescence. No risk factor was identified in 27 children. Hypercoagulable states (29%), cardiac disorders (24%), and arteriopathies (21%) were the most common risk factors. Some risk factor categories were more likely to be identified in isolation (i.e. cardiac disorders, prothrombotic abnormalities and chronic head and neck disorders) than others. The number of risk factors (n = 0–4) per patient and risk factor categories did not differ by age. Conclusion: Although we could not identify common patterns of risk factor combinations, several risk factors occurred more likely in isolation than others. Further research should focus on the impact of isolated presumed childhood stroke risk factors like certain prothrombotic abnormalities, migraine or a patent foramen ovale. With regard to different age groups, stroke mechanisms in male adolescents require particular attention. Highlights: The risk of childhood arterial ischaemic stroke depends on age and sex. There is a broad list of presumptive risk factors. The number of risk factors and risk factor categories do not differ by age. There are no clear patterns of risk factor combinations. Every childhood stroke requires complete and optimally standardized investigations.